ANALISIS PERBANDINGAN TEKNIK PENERJEMAHAN ISTILAH TABU DALAM FILM THE WOLF OF WALL STREET DAN DUA TERJEMAHANNYA (SUBTITLE RESMI VCD DAN AMATIR DARI SITUS SUBSCENE.COM) SERTA DAMPAKNYA PADA KUALITAS TERJEMAHAN - Sari, Nurul Intan; M.R., Nababan; Djatmika, Djatmika (PRASASTI: Journal of Linguistics, 2016)
This research is conducted by analyzing taboo words in The Wolf of Wall Street movie and its two subtitle versions. The aims of this research are to describe: (1) form and classification of taboo words found in The Wolf of Wall Street movie, (2) the translation techniques used for translating taboo word in The Wolf of Wall Street movie and its two subtitle version, (3) the translation quality of taboo words translations in VCD and amateur subtitles of The Wolf of Wall Street movie, (4) the impact of translation techniques toward the quality of taboo words translations in VCD and amateur subtitles of The Wolf of Wall Street movie.The research method applied is descriptive qualitative. In addition to that, it is embedded case study. The sources of data consist of documents and informants selected with purposive sampling technique. The documents are The Wolf of Wall Street movie and its two subtitle versions. Informants are validator and three raters. The data are taboo words that have been validated by validator and the information about translation quality given by raters. The techniques of collecting data are document analysis, questionnaire, and focus group discussion. The data were analyzed by using ethnography method composed by Spradley (1980)The findings show that there are two kinds of grammatical unit of taboo words, they are word and phrase. Sexual references and offensive slang are the dominant categories found in this research. In VCD version, the translation techniques used are established equivalence, reduction, amplification, literal, borrowing and generalization. Established equivalence creates high level of accuracy and acceptability. Reduction affects the quality with low level of accuracy but can create acceptable translations. Meanwhile, in the amateur version, there are seven translation techniques used. They are established equivalence, reduction, amplification, borrowing, generalization, literal, and compensation. This research finds that established equivalence makes the taboo words translations accurate and acceptable. Reduction and the other techniques results in the low level of accuracy but high level of acceptability. Based on the findings, it can be drawn that the translation techniques applied affect the quality of taboo word translations in term of accuracy and acceptability.Â Keywords: taboo words, translation techniques, accuracy, acceptability